Competitiveness of short sea shipping: the case of olive oil industry. Issue 8 (1st August 2016) - Galati, Antonino; Siggia, Dario; Crescimanno, Maria; Martín-Alcalde, Enrique; Saurí Marchán, Sergi; Morales-Fusco, Pau
Abstract : Purpose: This paper analyses the economic benefits of Short Sea Shipping (SSS) in the shape of Motorways of the Sea compared to road transport. The study cover a gap in agro-food economics and analyses the economic benefits of sea transport mode compared to road transport in the food trade between Spain and Italy for a specific product: olive oils. Design/methodology/approach: Three different transportation scenarios are considered (road only, road combined with accompanied SSS; and road combined with unaccompanied SSS) linking the main olive oil production and consumption areas in Spain and Italy. In each scenario the cost per unit shipped have been calculated. Findings: The results show the road option is about 30% and 34% more costly than the best Short Sea Shipping option available for the exportations from Jaén and Southern Catalonia, respectively. Research limitations/implications: The need of further research is identified, mainly focused in two directions: First, the need for inclusion of new variables to the model (e.g. value of time, seasonality, complexity of the transport chain, potential demand, etc.) to better assess the competitiveness of the sea connection and, secondly, a study of the environmental impact and socio-economic benefits of SSS implementation for the agri-food sector. Originality/value: The research enriches the current literature on this field and provides a basis for future studies. In particular, it corroborates the strategic decisions taken in the framework of European transport policy demonstrating a greater economic sustainability of SSS, and more specifically MoS, compared to the road transport.